A csicseriborsó (Cicer arietinum L.) gyomszabályozása a Szeged-Öthalom kísérleti területen - Kristó, István; Vályi Nagy, Marianna; Szarvas, Adrienn; Vojnich, Viktor József (GEORGIKON FOR AGRICULTURE, 2020)
Chickpeas (Cicer arietinum) are one of our oldest known and cultivated plants. However, as the reform diet spreads, it is becoming popular again and demand is expected to grow. It is cultivated mainly in countries where human protein needs are basically plant-based: India, Asia Minor and Mediterranean countries (Greece, Turkey, Italy, Spain, North Africa), USA and Mexico. It is an extremely drought-tolerant plant that can be successfully grown under harsh conditions without irrigation, which is becoming increasingly important with climate change. Today, very few herbicides are allowed in the cultivation of chickpeas. During the experiment were used four herbicides (Stomp Super, Basagran 480 SL, Corum, Pulsar 40 SL) and an adjuvant (Dash HC). Our aim is to understand the conditions under which chick peas are grown and to investigate the impact of the established weed control methods on our crop and its weed flora, including possible toxic effects.
Keywords: Chickpeas (Cicer arietinum); herbicides; weed control